Preparation to Face Minimum Competency Assessment in Elementary School - Retno Dwi Astuti; Eko Supriyanto; Yeny Prastiwi; Minsih Minsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
Minimum Competency Assessment (AKM) as a new assessment system needs to be addressed by the organized school by making various preparations. This study aims to describe the preparation in dealing with AKM in Elementary Schools (SD). This research is qualitative research with a phenomenological approach.The subjects in this study were principals and teachers of a public elementary school in the Eromoko sub-district, Wonogiri district. Data was collected by using observation, interview, and documentation techniques. Data analysis techniques using interactive analysis include data collection, reduction, presentation, and conclusion. The results showed that the AKM organizing education unit had prepared rooms and equipment by preparing a waiting room, AKM room, Chromebook, electricity and stable internet. Administrative preparation was done by printing and pasting the required documents. The preparation of students was done by providing socialization, practice about AKM questions using books, and training on the use of computers.